Tourism activities and companies in a sustainable adventure tourism destination: the Azores - João Ponte; Gualter Couto; Pedro Pimentel; André Oliveira (Tourism & Management Studies)
The Azores is one of the most sustainable nature-based island destinations in the world. Local tourism activities companies are vital to tourists’ adventure experiences. These businesses’ portfolios were analysed using various editions of the official Tourism Activities Guide. The analysis focused on companies’ products, types of activities, geographical coverage and brands. The generalised profile generated indicates that these firms each operate on only one island, have a small portfolio and are prone to specialise in sea or land activities. Snorkelling and motor boat rides are the most common sea activities, while nature hikes and walks, van tours and cultural tours are the most widely offered land activities. Explicit or indirect references to the Azores and adventure often appear in companies’ brands, which is in line with international trends in adventure tourism. However, company profiles are changing due to the impacts of a new air transport model.